2013
DOI: 10.3311/pptr.7108
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the Wetting Property and Electrical Conduction of Silver-Gold (Ag-Au) Alloys

Abstract: The wettability of graphite by the silver-gold (Ag-Au) liquid alloy was measured using the sessile drop method at a temperature interval of 1273 -1473 K. The measured alloys are in the solid solution range. The system is found poorly wetting with the contact angle at an interval of 112. . . 136 degrees. Typical alloying effects are found, as the Ag host metal is gradually replaced by Au alloying element. The results of the contact angle measurements were compared to the change of electrical resistance. The wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Previous studies [27,28,29,30,31] have provided values for ϵ,σ, and rc but, as explained in Supplementary Materials, Figure S1, we found that none of these sets of values were able to reproduce the contact angle of pure Ni and Ag liquid droplets deposited on graphite. Here, we find that using the values in Table 2 for ϵ,σ, and rc, respectively, we obtain a contact angle of 59 for Ni on graphite, and 145 for Ag on graphite; these theoretical contact angles are very close to the values found experimentally (Ag-C = 135 and Ni-C = 60) [32,33,34,35,36,37]. All the simulations were done with the software LAMMPS [38].…”
Section: Methodssupporting
confidence: 81%
“…Previous studies [27,28,29,30,31] have provided values for ϵ,σ, and rc but, as explained in Supplementary Materials, Figure S1, we found that none of these sets of values were able to reproduce the contact angle of pure Ni and Ag liquid droplets deposited on graphite. Here, we find that using the values in Table 2 for ϵ,σ, and rc, respectively, we obtain a contact angle of 59 for Ni on graphite, and 145 for Ag on graphite; these theoretical contact angles are very close to the values found experimentally (Ag-C = 135 and Ni-C = 60) [32,33,34,35,36,37]. All the simulations were done with the software LAMMPS [38].…”
Section: Methodssupporting
confidence: 81%
“…Research of component material of the reinforcing, influenced by brazing process [1], performed at SEM microscope, does not reveal defects such as crack, figure 6 Figure 7 presents the penetration through the capillarity of brazing material, in the gap of the joint and finishing of the grain structure of the returning base metal in the vicinity of the filler material, a phenomenon that can be explained by the overlapping effect of thermal cycles produced at brazing with the thermal treatments of returning for supports, in semi fabricated condition [7].…”
Section: Innovative Technologies For Joining Advanced Materials VIIImentioning
confidence: 99%
“…The interfaces which are produced can be solid/liquid, solid/gas or solid/liquid, liquid/gas or liquid/liquid. Wettability is most often described by the geometry of a sessile or resting drop (Hlinka and Weltsch, 2013). Contact angle (θ) is a measure of wettability and is defined as the angle between the surfaces of the liquid and the solid substrate at the line of contact, as measured from the side of the liquid.…”
Section: Introductionmentioning
confidence: 99%